Trinidad, Port of Spain. Hindu girl - (:unkn) unknown (Associated Screen News Ltd, Montreal [Printed in Canada], 2009)
Woman of East Indian origin filling water by a standpipe. Located on the right and at the bottom of the postcard is "P588". At the back of the card is printed "This is a Real Photograph" and also printed at the back of the card in upper-case is "CANADIAN PACIFIC CRUISE."
Colour: Black and white;Style: Portrait; Other:Bordered,Divided
Keywords: Postcards; Trinidad and Tobago